Aplikasi Bian Lian Pada Interior Pusat Informasi Sejarah Tionghoa Peranakan di Surabaya - Fenny Carolina Sutanto; Stephanus P Honggowidjaja; purnama esa dora tedjokoesomo (Intra, 2014)
Surabaya is one of many cities in Java that has many chinese descendant citizen. In the history of Surabaya, peranakan chinese have quite significant role especially in term of economics. However, history pertaining to the chinese tribe, especially culture are rarely available and has been substantially marginalized during the Orde Baru period. This causes most of chinese descent, especially young people in the modern era do not know how the history of their ancentors. In addition, young people nowadays are increasingly losing their interest in learning about history because it is difficult to learn and tedious. Therefore, it is necessary to provide a recreative and innovative chinese historical center in Surabaya to introduce the history about Surabaya chinese descendant especially about economy, social, architecture, politic, and literature. Additionally, this historical center will also introduced about Java chinese descendant culture.